A Theory of the Temporal Asymmetry of Deliberation. (26th June 2013) - Navabi, Ali Akbar
Abstract: Contemporary theories of the temporal asymmetry of deliberation seek the origins of the asymmetry either in the physics of the early universe or in the epistemic orientation of agents. An attempt is made in the following lines to consolidate the rival thesis that the temporal asymmetry of deliberation is rooted in an ontological divide between the past and the future. I argue that agents can deliberate about the future but not the past because while the past is in a sense real, the future is nothing at all. The argument for the thesis includes striking a connection between deliberation and truth on the one hand and truth and being on the other. The argument thus proceeds, via a modal principle, from the asymmetry of deliberation into the semantics of propositions about the past, the present, and the future and from there to the ontology of the past, the present, and the future. The 'ticket' for transition in the argument from semantics to ontology is a truth‐making principle, according to which propositions are true or false in virtue of an existing reality.